Artistic autonomy in non-autonomous contexts: reframing collective agency and insurgence from Caribbean artist-managed spaces - Garrido Castellano, Carlos (2017)
This article engages the debates on collective agency, autonomy, institutional practices and socially engaged art by comparatively analyzing the activity of two Caribbean artist-managed spaces which emerged in the first decade of the twenty-first century: BetaLocal in Puerto Rico and L’Artocarpe in Guadeloupe. Based on fieldwork research and interviews with artists and art audiences, the examination of both projects will be driven by three main objectives: the first has to do with assessing in which ways both initiatives are shaped by their emergence in territories still attached to political and economic bonds. Secondly, I attempt to measure how both collective artistic organizations can approach the material conditions of cultural (re)production and autonomy, confronting the restrictions of Puerto Rican and Guadeloupean cultural and economic policies. Finally, I intend to locate my case study within a global panorama of socially engaged and collaborative artistic practice. From this perspective, I assert that collaborative practices emerging in still dependent contexts constitute a privileged viewpoint in order to examine issues of collective agency, empowerment and alternative futures.